Chatbot de asistencia virtual en la plataforma institucional de gestión académica de la ESPAM MFL - Rivas Párraga, Juan Carlos (2021)
The objective of this work was to implement a virtual assistance chatbot in the Academic Management System of at ESPAM MFL, in order to offer users assisted solutions and execution of tasks, such as: searching for manuals and documents in general, password changes, academic inquiries, etc. To fulfill this objective, the SCRUM methodology was applied, which provides a framework divided into three stages (planning and architecture, execution of development, inspection and adaptation of development) thus helping in the effectiveness of the project. In the planning and architecture stage, both functional and non-functional requirements were taken into account for the elaboration of the database and use case diagrams. In the execution phase of the development, the interface was created and the chatbot corpus was filled in using a knowledge base registration panel, since being a word spotting type chatbot, it is necessary to have a registry of the keywords with what the bot would have access to the responses for the user. In the inspection and adaptation stage, the tests and respective implementation were carried out so that the end user interacts with the system and thus be able to obtain the answers they want to receive. The result obtained is a module integrated into the Academic Management System at ESPAM MFL, which makes it easier for users to search using keywords.